Penerapan Algoritma Wall Following Pada Robot Quadruped Pemadam Api - Tumbel, Bryan; Poekoel, Vecky C.; Kambey, Feisy D. (Universitas Sam Ratulangi, 2018)
Abstrak – Today there is already a fire suppression device such as Smoke Detector, Fire Sprinkler and Heat Detector, it works passively because these tools cannot find the location of the fire source directly. Therefore, a fire extinguisher quadruped robot is made, with the important process of wall following algorithm, it is known that the wall following algorithm is an algorithm that follows the wall as an object that can guide the robot's path to find and extinguish the hotspots. A research was made on the Application of the Wall Following Algorithm in the Quadruped Fire Extinguisher Robot to answer these problems with research and development methods where the tests have been carried out such as testing the wall following algorithm, and testing the sensors in order to support the hotspots searching, the conclusions in this research was successfully applied to the quadruped fire extinguisher robots by obtaining an average time of 3.59 minutes to locating and extinguishing fires in 12 room configurations. Keywords: Algorithm, Hotspots, Quadruped Robot, Wall Following. Abstrak – Pada saat ini sudah terdapat sebuah alat pencegah kebakaran seperti Smoke Detector, Fire Sprinkler dan Heat Detector tetapi cara kerjanya hanya bersifat pasif karena alat-alat tersebut belum bisa menemukan letak posisi sumber api secara langsung. Oleh karena itu dibuatlah robot quadruped pemadam api dengan proses pentingnya yaitu algoritma wall following, diketahui algoritma wall following adalah algoritma mengikuti dinding sebagai objek yang dapat menuntun perjalanan robot mencari dan memadamkan titik api. Maka dari itu dibuatlah penelitian Penerapan Algoritma Wall Following Pada Robot Quadruped Pemadam Api untuk menjawab permasalahan tersebut dengan metode penelitian dan pengembangan dimana dalamnya sudah dilakukan pengujian-pengujian seperti pengujian algoritma wall following, serta pengujian sensor-sensor agar dapat menunjang pencarian titik api, kesimpulan dalam penelitian ini algoritma tersebut berhasil diterapkan pada robot quadruped pemadam api dengan memperoleh waktu rata-rata 3.59 menit dalam mencari dan memadamkan api pada 12 konfigurasi ruangan. Kata kunci: Algoritma, Robot Quadruped, Titik Api, Wall Following.